A facile AuNPs@aptamer-modified mercaptosiloxane-based hybrid affinity monolith with an unusually high coverage density of aptamer for on-column selective extraction of ochratoxin A. Issue 21 (1st October 2018) - Chi, Jinxin; Chen, Maolin; Deng, Lijun; Lin, Xucong; Xie, Zenghong
Abstract : A facile AuNP@aptamer-modified affinity monolith was fabricated with unusually high coverage density of aptamers for on-column high-sensitivity extraction. Abstract : A convenient and high-performance AuNPs@aptamer-modified mercaptosiloxane-based hybrid affinity monolithic column with an unusually high coverage density of aptamers was facilely prepared and used for on-column selective recognition of ochratoxin A (OTA). Due to the high surface-to-volume ratio of AuNPs, the robust conjugation of Au-SH and large specific surface area of hybrid-silica monolith, high coverage density of 5′-SH-aptamers up to 3494 pmol μL −1 was achieved, which was 2.5–10 folds higher than that of other previously reported affinity monoliths modified with AuNPs@Apt. Using OTA as the model analyte, the highly selective recognition of OTA was carried out via online coupling with HPLC, and the cross-reactivity towards analogues, such as OTB and aflatoxin B1, was weak. High recovery yields of OTA were achieved at more than 92% ( n = 3) even when OTB was added at a high concentration level up to 50 ng mL −1 . For sample analysis, efficient discrimination of OTA was successfully obtained with a sensitive detection limit of 25 pg mL −1 . The recoveries of OTA with different fortified levels were achieved at 88.6%–94.1% and 88.2%–94.3% for beer and wine samples, respectively. This protocol provides a facile approach for fabricating a desirable affinity monolith modified with abundant aptamers for highly selective and sensitive on-column extraction of target analyte OTA.